Study of the Characterization of Partial Purified Polyamine Oxidase from Sheep's Brain Tissue - Wathba Ali; Sarah Younis (College of Education for Pure Sciences, 2019)
The study included partially purified of polyamine oxidase (PAO) from sheep's brain tissue by dialysis and ion exchange chromatography using DEAE-cellulose techniques. Tow isoenzymes (I،II) were obtained with specific activities 3.876 and 2.856 units/ mg of protein and purification folds 11, 8 times respectively compared with crude enzyme. The specific activity of PAO I was better than PAO II, thus we considered it for following studying. The optimal condition showed 100 μL volume of enzyme, pH=9, 40ͦ C, at incubation time 10 min. Some of properties of partially purified PAO enzyme were studied and the specificity was found to be superior to the base material, where it was given the highest activity when using spermidine. Using lineweaver_ Burk plot, the values of maximum velocity (Vmax) and Michaelis constant (Km) were found to be 0.145 Unit/ ml and 43.4 mM respectively, and potassium ion was the most activator ion to the enzyme arrived to 233.8%. The compounds (ammonium chloride, sodium fluoride, phenyl hydrazine, sodium azide and EDTA) showed a significant inhibitory effect on the activity of the enzyme (56.1%, 49.9%, 49.9%, 37.3% and 25%) respectively.